Організація і методика бухгалтерського обліку та контролю запасів за матеріалами АТ «Фармак» - Желязков, Ігор Сергійович; Zhelyazkov, Ihor Serhiyovych (Ірпінь, 2023)
Дослідження базується на розробці щодо вдосконалення організації і методики обліку та контролю запасів, а також визначення можливостей використання сучасних методик обліку та контролю для покращення фінансових результатів діяльності підприємства. Для вдосконалення методики і організації обліку виробничих запасів, рекомендовано перейти АТ «Фармак» на програмний продукт BAS Бухгалтерія. Щодо обліку запасів, дана програма контролює наступні аналітичні параметри: підтримка складського та партійного обліку; облік додаткових витрат, що включаються до вартості запасів; облік транспортно-заготівельних витрат; документи по складському обліку, включаючи комплектацію.

The essence and content and significance of accounting and analytical support as an important component of a complex system of economically safe and sustainable development of the enterprise are considered. Based on the results of the research, proposals were formulated regarding the formation of accounting and analytical support for the enterprise. In particular, recommendations on the development of an accounting policy that would ensure economically safe activities and sustainable development of the enterprise, as well as contribute to the formation of reliable information for the needs of users. The directions for improving the company's reporting in terms of sustainable development have been determined.
Organization and methodology of accounting and inventory control based on JSC "Farmak" materials
Keywords: запаси; обліку запасів; організація і методика обліку запасів; контроль операцій з запасами; inventory; inventory accounting; organization and methodology of inventory accounting; control of inventory transactions